Spatial distribution of soil quality under different vegetation types in the Yellow River Delta wetland - Sun, Debin; Li, Yunzhao; Yu, Junbao; Li, Baoquan; Guan, Bo; Zhou, Di; Wang, Xuehong; Yang, Jisong; Ma, Yuanqing; Zhang, Xin; Li, Xue; Ling, Yue; et al. (Frontiers in Ecology and Evolution, 2022)
The soils from four typical natural wetlands, namely, Phragmites australis, Tamarix chinensis, Suaeda salsa, and tidal flat, as well as reclaimed wetland, were selected to evaluate the soil quality in the Yellow River Delta. Fourteen soil physicochemical property indexes were employed to build a minimum data set (MDS). Combined with vegetation type and soil depth, the soil quality index (SQI) was conducted. A fuzzy logic model was applied for data normalization. The contrast test was conducted to verify the accuracy of the MDS. The results showed that the MDS consists of TOC, NO3--N, soil salinity, TS, TP, Mg, C/N and pH. The soil quality decreased from the inland to the coastline and from reclaimed wetland to tidal flat with the change of vegetation type. The soil quality of 0–10 cm soil depth was better than that of 20–30 cm soil depth. The soil qualities of reclaimed land were significantly better than those of natural wetlands at the same soil depth. Correlation analysis results showed that agricultural reclamation has become an important factor of soil quality change in the study area. Comparative results of two methods of MDS and the total data set (TDS) testified that the method of MDS was credible and accurate for soil quality assessment of the study area. Our results indicated that wetland protection and agricultural reclamation in coastal areas should keep a rational balance.